Effect of the B chromosome-located long non-coding RNAs on gene expression in maize - Xin Liu; Wenjie Yue; Shiqi Lin; Yuxian Yang; Tong Chen; Xiaowen Shi (Crop Design)
Using artificial chromosomes in maize breeding allows for site-specific integration of multigene stacks, effectively overcoming the limitations of conventional transgenic approaches. The maize B chromosome, which is dispensable and highly heterochromatic, has minimal impact on phenotypes at low copy numbers, making it a promising platform for engineering artificial chromosomes. However, recent studies have demonstrated that the maize B chromosome can impact gene expression and recombination on the A chromosome. Understanding the genetic characteristics of the B chromosomes and their impact on gene expression is essential for their application in artificial chromosome construction. Despite advancements in elucidating how the B chromosome affects A chromosome expression, the role of long non-coding RNAs (lncRNAs) in this context remains unclear. In this study, we analyzed the RNA-seq data from leaf tissue of plants with 0–7 ​B chromosomes, identifying a total of 1614 lncRNAs, including 1516 A chromosome-located and 98 ​B chromosome-located lncRNAs, 72 of which are specific to the B chromosome. While A-located lncRNAs show greater dependence on the mere presence of the B chromosome, the expression of B-located lncRNAs is significantly affected by the number of B chromosomes present. Regulatory networks constructed in this study suggest that B-located lncRNAs may drive the differential expression of A chromosome-located transcription factors and genes associated with circadian rhythm regulation, indicating their regulatory role in A chromosome gene expression.